Prevalence and associated factors of MAFLD in adults with type 2 diabetes. - Yifei He; Feng Xiao; Bin Yi; Jin Lu (PLOS Global Public Health)
To estimate the prevalence and associated factors of hepatic steatosis and fibrosis in adults with type 2 diabetes (T2DM) in the United States.Data were retrieved from the 2017‒March 2020 prepandemic cycle of the National Health and Nutritional Examination and Survey (NHANES). The study population included patients with T2DM. The controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) were used to assess hepatic steatosis and fibrosis, respectively. A total of 1,290 T2DM patients were included, 85.2% (1044 patients) of whom presented with hepatic steatosis (CAP>248 dB/m). Among the 1044 T2DM patients with metabolically associated fatty liver disease (MAFLD), 29.5% developed hepatic fibrosis (LSM>8 kPa). Non-Hispanic black individuals (adjusted OR = 0.4008), BMI (adjusted OR = 1.1627), HbA1c (adjusted OR = 1.1450), TG (adjusted OR = 1.2347), HDL (adjusted OR = 0.4981), ALT (adjusted OR = 1.0227), AST (adjusted OR = 0.9396), and albumin (adjusted OR = 1.7030) were independently associated with steatosis. Age (adjusted OR = 1.0300), female sex (adjusted OR = 0.6655), BMI (adjusted OR = 1.1324), AST (adjusted OR = 1.0483), and GGT (adjusted OR = 1.0101) were independently associated with fibrosis. Heart failure was an independent factor associated with advanced fibrosis (adjusted OR = 1.9129) and cirrhosis (adjusted OR = 2.228). In the United States, hepatic steatosis is highly prevalent among T2DM patients, with 29.5% of these patients developing hepatic fibrosis. Some components of metabolic syndrome are related to hepatic steatosis and fibrosis. Moreover, heart failure is an independent factor associated with advanced fibrosis and cirrhosis.